Hydrodynamic cavitation assisted recovery of intracellular polyhydroxyalkanoates - Yilmaz Nayir, Tuelin; Kucukaga, Yusuf; Kara, Serdar (Springer, 2025)
In this study, the hydrodynamic cavitation (HC) process was adopted for the recovery of intracellular biopolymer, namely polyhydroxyalkanoates (PHAs), from mixed microbial culture (MMC). To investigate the potential and performance of HC process, two cavitation devices (orifice-1 and orifice-17) were employed. The impact of biomass concentration, orifice type and pressure differential on recovery yield was assessed. The HC-assisted PHA recovery protocol introduced a novel technique that uses HC for cell disruption and a solvent for biopolymer separation. The results demonstrate the feasibility of obtaining biopolymer within a short operation time (5 min), achieving 72% process efficiency using the HC-assisted recovery procedure. The biopolymer recovered via HC at optimal conditions exhibited a purity of 71.4%, indicating effective polyhydroxybutyrate (PHB) isolation. Its molecular weight of 0.15 x 10(6) g/mol aligns with typical PHB ranges, suggesting its suitability for various applications. Fourier-transform infrared spectroscopy (FTIR) analysis confirmed compatibility with commercial PHB. Thermal degradation profiles showed slightly lower stability compared to commercial PHB, with a 10% mass loss at 243.21 degrees C and a maximum degradation temperature of 262.12 degrees C. Despite these minor differences, HC presents a promising, greener method for PHA recovery, offering potential applications in sustainable industries.
Keywords: Bioplastic; PHA; PHB; Hydrodynamic cavitation; Biopolymer extraction; Mixed microbial culture